Management of instruments separated intracanally during endodontic treatment - Pietrzycka, Krystyna; Pawlicka, Halina (Journal of Stomatology, 2016)
Introduction. The chemo-mechanical preparation of the canal involves the use of hand and/or rotary files. There are no perfect endodontic instruments, resistant to mechanical wear or procedural errors. The application of excessive force or improper technique during the procedure, the overuse of NiTi rotary files, as well as the complicated root canal anatomy, may cause separation of an endodontic instrument inside the root canal. Aim of the study. To describe cases of patients who presented with intracanal instruments broken during endodontic treatment (and subsequently treated by the authors of this study), and to present different management procedures. Conclusions. Removal of a broken endodontic instrument from the root canal is a complex and difficult procedure that requires skill, dexterity, knowledge of the root canal system anatomy, as well as appropriate equipment and facilities. The presence of a broken fragment should not adversely affect the outcome of root canal treatment.